Fibrillar Type I Collagen Enhances the Differentiation and Proliferation of Myofibroblasts by Lowering α2β1 Integrin Expression in Cardiac Fibrosis. (30th January 2017) - Hong, Jian; Chu, Ming; Qian, Lijun; Wang, Junhong; Guo, Yan; Xu, Di
Abstract : Many studies have shown that α 2 β 1 integrin plays an important role in the development of cardiac fibrosis. However, the mechanism of how α 2 β 1 integrin regulates the differentiation and proliferation of myofibroblasts in cardiac fibrosis through fibrillar collagen (FC) remains uncertain. We established that FC mimicked the 3-dimensional extracellular matrix (ECM) of fibroblasts from post-myocardial infarction (MI) patients in vivo. This allowed us to explore the differentiation and proliferation of cardiac fibroblasts on FC. Here, we report that low expression of α 2 β 1 integrin increased protein kinase B (AKT) activation and α -smooth muscle actin ( α -SMA) expression. This occurred due to the instability of phosphatase and tensin homolog (PTEN) in myofibroblasts on FC. We also demonstrated that FC reduced protein phosphatase type 2A (PP2A) activity of myofibroblasts, which was coincident with low α 2 β 1 integrin expression and activation of AKT, but not mitogen-activated protein kinase (ERK). In addition, knock-down of both β 1 integrin and PP2A in fibroblasts promoted differentiation and proliferation via AKT activation and increased α -SMA expression. In summary, our study demonstrated that low α 2 β 1 integrin expression regulated its downstream targets PTEN and AKT via crosstalk with PP2A, a critical cell signaling pathway that permits aberrant differentiation and proliferation of myofibroblasts on FC.